Analisis Manajemen Rantai Pasok Susu Segar untuk Peningkatan Kinerja: Studi Kasus KSU Tandangsari, Sumedang - Deddy Supriyadi; Chusein Waliyulloh (J-Coop : Journal of Co-operative, 2025)
This study aims to analyze the implementation of fresh milk supply chain management at KSU Tandangsari Tanjungsari Sumedang from the perspective of its flows and performance. The theoretical framework used in this research includes Supply Chain Management Theory, Supply Chain Flows, and Supply Chain Performance. This research is quasi-qualitative, employing a case study method. The data consists of both primary and secondary sources, incorporating qualitative and quantitative aspects. Data collection was conducted through observation, interviews with informants, document analysis, and literature review.The results indicate that: 1) The supply chain flows, which include material flow (fresh milk), financial flow, and information flow, run smoothly without significant obstacles. If any issues arise, KSU Tandangsari is prepared to address them promptly, 2) The overall supply chain performance is considered good, although not yet optimal, as the cooperative operates under capacity, particularly in its cooling unit. This is due to a significant decline in milk production, currently averaging only 10,000 liters per day, whereas the full capacity of the cooling unit is 37,500 liters. If the cooperative can maximize asset utilization, it will improve supply chain performance, especially in terms of operational cost efficiency (milk handling costs).